Biopriming of Momordica charantia Seeds with Enterobacter to Improve Nutritional and Biochemical Attributes - Shazia Anwer Bukhari; Nabila Farah; Ghulam Mustafa; Sibtain Ahmed; Mohammed Fahad Albeshr (Journal of Food Quality)
The increasing world population needs a standard balanced diet to address malnutrition problems. For this purpose, seed priming is one of the best techniques, which helps to increase the production of functional and nutritional food crops. Different techniques have been used for seed priming, but biological priming is the most frequently used because biocontrol agents offer a friendly environment for the growth of food crops. In this study, Momordica charantia L. seeds were subjected to a strain of Enterobacter sp. FD17 as a biocontrol agent at different time exposures (i.e., 24 h, 48 h, and 72 h). Leaf growth, flavonoids, chlorophyll content, amino acids, soluble sugars, protein, and total soluble phenolics were studied in the vegetative stage. The yield of nutritive components was evaluated from fruit, peel, and pulp of M. charantia. Biopriming was revealed to improve the final emergence rate, mean emergence time, seedling vigor, emergence index, and vigor indices I and II. Among the growth parameters, the root (0.45 ± 0.045 g) and shoot fresh weight (1.23 ± 0.05 g), leaf area (15.52 ± 1.5 cm), shoot length (30.33 ± 0.58 cm), number of flowers (6 ± 1.0), fruit weight (96.33 ± 1.15 g), and germination percentage (56.67 ± 11.55%) were also improved. Among biochemical analyses, biopriming improved chlorophyll a (6.33 ± 0.58 mg/g) and b (8.58 ± 2.5 mg/g), total soluble sugar (33.13 ± 2.24%), and total chlorophyll content (9.0 ± 1.5 mg/g). The nutritional analysis showed that free amino acids (1.43 ± 0.02 mg/g), total soluble sugar (42.53 ± 1.65%), ash (20.53 ± 2.57%), and catalase (347.47 ± 34.76 U/g) were increased in fruit, while crude fiber (3.62 ± 0.1%) and peroxidase (5.61 ± 0.34 U/g) in peel and protein and metabolizable energy in peel and fruit were increased. Among the water, acetone, and methanol extracts, the maximum antibacterial activity was shown by methanol extracts of leaves against Gram-negative and Gram-positive bacterial species (i.e., Pseudomonas aeruginosa and Staphylococcus aureus, respectively) with inhibitory diameters of 3 mm. Biopriming also improved the phenolic contents in the leaves and fruits of M. charantia. Biopriming treatment was also revealed to be directly correlated with antiglycation activity. Therefore, biopriming treatment on seeds could be used to manipulate plant cell metabolism with a substantial improvement in phenolic content, antibacterial activity, and growth of M. charantia.